PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA VIDEO TERHADAP KESIAPAN IBU HAMIL DALAM MENGHADAPI PERSALINAN - lisnawati, lisnawati; Linggar Adi Prahastuti, Dara (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
Problems : The indirect cause of maternal death is that there are still many late cases. Case 3 is late, including: being late in recognizing the danger signs of childbirth and making decisions, being referred too late to a health facility, being late being handled by health workers at a health service facility. Readiness in the face of childbirth is one solution to prevent maternal death. The aim of the research: to determine the effect of health education using video media on the readiness of pregnant women in facing childbirth in the working area of ​​UPTD Puskesmas Talun, Cirebon Regency. Method: The research design used a quasi-experimental design with pretest and posttest with one group design. The sampling technique was carried out by non-probability sampling technique. Sampling used a total sampling technique (30 pregnant women) in the second and third trimesters. Bivariate analysis using Wilcoxon test. Results: The results of the pre test and post test showed an increase. The effect of health education using video media on mother's readiness in facing childbirth (p value = 0.000). Conclusion: There is an effect of health education using video media on the readiness of pregnant women in facing childbirth. Keywords: Health Education Using Video Media, Readiness, Pregnant Women